Trend of adherence to iron supplementation during pregnancy among Ethiopian women based on Ethiopian demographic and health surveys: A Multivariable decomposition analysis - Delie, Amare Mebrat; Gezie, Lemma Derseh; Gebeyehu, Asaye Alamneh; Tarekegn, Gebrekidan Ewnetu; Muche, Achenef Asmamaw (Frontiers in Nutrition, 2022)
Background: Iron deficiency is one of the significant factors of anemia during pregnancy, and iron supplementation is the main method of prevention and control of lack of iron anemia, and its effectiveness depends on adherence to the iron supplement. Methods: This study was based on 2005, 2011, and 2016 EDHS data. After the data was weighted, 696, 1282, and 3096 in 2005, 2011, and 2016 EDHS data, respectively, were used for final analysis. The data was edited, cleaned, coded, managed, and analyzed using Stata Corp version 16 software. Logit-based multivariable decomposition analysis was used to identify variables significantly associated with the change in adherence level during pregnancy. Results: Adherence levels increased from 1.1% in the 2005 EDHS to 12.4% in 2016. About 30.9% of the overall change in adherence level to iron supplement use during pregnancy was due to the difference in women’s socio-demographic-related variables. After adjusting for those compositional changes, around 69.1% of the change in the adherence level was because of the difference in the coefficients (behavioral related variables). Among behavioral characteristics, women's age groups, rich wealth index, and secondary and above-secondary educational status of their husbands had a statistically significant effect on the positive change in the adherence level of pregnant mothers. The adherence level to iron supplement use during pregnancy has increased significantly over the last decade in Ethiopia. Both the compositional and behavioral characteristics of women play a major role in the increasing trend of adherence levels.